Lietuviams būdingos gramatinės anglų kalbos klaidos - Aprijaskytė, R.; Pareigytė, E. (Kalbotyra, 1973)
In this paper an attempt is made to analyse the most common grammar errors made by Lithuanian learners due to the interference of their mother tongue. The analysis of the errors shows that most of them are due to: 1) the different expression certain grammatical categories find in the Lithuanian and English languages, 2) the different sentence structure and 3) different government.1. Mistakes caused by the different expression grammatical categories find in both languages are: a) mistakes in the usage of number (replacing singular by plural and vice versa); b) mistakes in the usage of tenses (neglecting sequence of tenses, replacing a present tense in adverbial clauses of time and condition by a future tense, replacing Present Perfect by Past Indefinite and vice versa, usage of should (would) + Infinitive in sentences of unreal condition not only in the principal clause, but also in the adverbial clause); c) mistakes in the usage of reflexive pronouns after verbs the Lithuanian equivalents of which are verba reflex.iva; d) mistakes of replacing the definite article by a demonstrative pronoun and the indefinite article by the indefinite pronoun one.2. Mistakes caused by the different sentence structure in both languages are: a) mistakes in word order (placing the object before the subject, inserting an adverbial modifier between the 1Iubject and the predicate, neglecting the sequence of attributes, using inverted word order in indirect questions); b) omission of parts of the sentence (the subject, part of the predicate); c) double negation.3. Mistakes due to different government in both languages are: a) replacing adverb by adjective and gerund by infinitive; b) mistakes in the use of objects (replacing prepositional object by indirect object without preposition, direct object by prepositional object, complex object by object clause). An awareness of the points of interference of the Lithuanian grammatical structure with that of English may enable the teacher to anticipate problems when presenting certain features of English grammar and planning techniques and materials aimed at overcoming them.